Waktu Penggunaan Kontrasepsi Pil Kombinasi yang Berhubungan dengan Kasus Kenaikan Tekanan Darah dalam Wilayah Kerja Puskesmas Martapura I Kabupaten Banjar Provinsi Kalimantan Selatan - Nirwana Perangin-angin (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2020)
The use of combined pill contraception is one of the causes of an increase in blood pressure, especially in the working area of ​​Martapura I Public Health Center, Banjar Regency, South Kalimantan Province, which is 26.32%. This study was conducted with the aim of knowing the Time of Use of Combination Pill Contraception Related to the Case of Increasing Blood Pressure in the Work Scope of Martapura I Public Health Center, Banjar Regency, South Kalimantan Province. The method used in this research is analytic survey with cross sectional approach. The population in this study were 234 acceptors and samples were 71 acceptors using the Purposive Sampling technique. The analysis used was the Chi Square test with α 0.05. The research results obtained p = 0.002. The conclusion of this study is that there is a relationship between the time of use of combined pill contraception with a case of increased blood pressure.